Development and Studies of New Magnetic Core@Shell Nanostructures - Dee, Garret (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
In this work, the synthesis of various magnetic nanoparticles such as magnetite, manganese ferrite, cobalt ferrite and copper ferrite is explored using different synthetic protocols. The produced nanomaterials are characterised by TEM, VSM, FTIR and XRD to get a qualitative and quantitative understanding of the material. Selected nanoparticles are further stabilised and protected with citrate and silica and these modifications are quantified by DLS to understand the effect of the coatings on the stability of the magnetic nanoparticles. The modified magnetic nanoparticles are further characterised by TEM, VSM, FTIR and XRD to understand any changes that have taken place, such as concerning morphology and the magnetic characteristics. It was found that a thicker silica shell reduced the magnetisation of the nanoparticles more significantly but to form a thinner shell was more difficult with agglomeration of the nanoparticles developing with a thinner shell. Selected silica coated magnetic nanoparticles and selected bare nanoparticles were functionalised with catalytic shells of manganese dioxide and cerium dioxide. The outcomes of these coating procedures were excellent with clear shells of both materials formed on the surface of the magnetic nanoparticles as viewed with TEM images. Further characterisations such as XRD, EDX and FTIR confirmed this result. These catalytic shell magnetic nanoparticles were then tested in various applications such as catalytic oxidation of benzyl alcohol to benzaldehyde, for inhibition of a reaction and reactivation after magnetic removal of the nanoparticles and for water remediation with dye contaminant removal. The manganese dioxide and cerium dioxide coated nanoparticles were found to perform poorly for the catalytic oxidation. The manganese dioxide coated particles were found to be successful for the inhibition and reactivation testing for a glue formulation. For the water remediation application, which was quantified by UV-vis spectroscopy, there was a variation of between dyes for the nanoparticles with some dyes showing excellent removal with the particles being recyclable after magnetic removal and heating to burn off the organic residue. This work also looked at coating a 2D material, boron nitride nanosheets with magnetic nanoparticles. This was with the viewpoint to create a nanofiltration membrane that could be recycled by magnetic heating. The synthesis were successful in creating excellent to good coverage on the 2D sheets with magnetic nanoparticles as observed by TEM and SEM analysis. The created nanocomposite membranes worked well in removing dye pollutant from water with filtration through the membrane. Further testing in in progress to test for the possibility of magnetic regeneration of the membrane.
APPROVED
Keywords: magnetic nanoparticles